Edukasi dan Interactive Nursing Reminder dengan Pendekatan Self Management untuk Meningkatkan Kepatuhan Minum Obat dan Kualitas Hidup Pasien Tuberculosis - Faisal Faisal; Rini Rachmawaty; Elly L Sjattar (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
This study aims to determine the effect of education and interactive nursing reminder based on Whatsapp with a self-management approach on quality of life and medication adherence in TB patients. The method used in this study is a quasi-experimental type, with a pre-test and post-test control group design carried out at the Puskesmas in the work area of ​​the Pangkep District Health Office. The sample in this study was selected by simple random sampling. The results showed that the patient's quality of life and adherence to medication for TB in the intervention and control groups was p = 0.000 (< 0.05), meaning that there were significant differences in the quality of life of patients and adherence to medication for TB patients between the treatment group and the control group. In conclusion, education and interactive nursing reminder based on Whatsapp with a self-management approach significantly affect the patient's quality of life and adherence to medication for TB patients. Keywords: Education, Interactive Nursing Reminder, Drug Compliance, Patient Quality of Life, Tuberculosis